Outage and BER performances of indoor relay‐assisted hybrid RF/VLC systems. Issue 17 (25th September 2018) - Namdar, Mustafa; Basgumus, Arif; Tsiftsis, Theodoros; Altuncu, Ahmet
Abstract : In this study, the authors analyse the outage performance of the indoor relay‐assisted hybrid radio frequency (RF)/visible light communication (VLC) systems. They derive closed‐form expressions for the outage probability of the end‐to‐end signal‐to‐noise ratio. Then they obtain the optimal approximation parameter with optimising the outage probability using the differential evolution algorithm. Moreover, they analysed the average bit error rate (BER) performance of the hybrid RF/optical system using pulse position modulation method while assuming the timing error in synchronisation. Finally, they present some numerical results utilising the newly derived exact closed‐form expressions.